The Impact of Organizational Spirituality on the Successful Implementation of Policies (Corporate Commerce) in Light of Mediating and Moderating Variables - Ahmadkhani, Masoud; Taherpour kalantari, Habibollah (Management Strategies and Engineering Sciences, 2023)
Today, employee ethics and spirituality within organizations are critical topics for managers. Individuals prefer to be present in the workplace with their three existential dimensions: physical, emotional, and spiritual. However, despite the growing trend in the research literature, robust studies and theories in this area remain limited. This study examines the effect of organizational spirituality on policy implementation and identifies the factors influencing policy performance from an Islamic perspective. The relationships between these factors are then assessed. The statistical population includes employees and managers from selected governmental organizations in Yazd city, and cluster sampling was used. The research is applied in its purpose, and data were collected through a validated survey questionnaire. A total of 392 questionnaires were prepared and distributed. Using exploratory factor analysis, the constructs comprising the conceptual framework variables were identified. Subsequently, based on hypothesis formulation, the identified factor structures were tested to confirm the relationships between constructs and components. These hypotheses were evaluated using confirmatory factor analysis with the help of LISREL 8.5 software. The PLS software was also employed to process the research model. The findings demonstrated that spirituality dimensions have a direct impact on job satisfaction, work-family balance, organizational culture, organizational commitment, and servant leadership. Additionally, job satisfaction, organizational culture, and servant leadership have a significant and direct impact on the performance of policy implementation.